2017
DOI: 10.1021/acs.energyfuels.7b00057
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Evaluation of Oil–Water Two-Phase Flow Using a Method Based on Terahertz Time-Domain Spectroscopy

Abstract: Oil–water two-phase flow widely exists in the petroleum industry, such as crude oil production and transportation. The flow pattern and slip phenomenon of oil–water two-phase flow have an important impact on the rational design and management of oil wells and pipelines. Because of the extremely high sensitivity of the terahertz wave to hydrogen bonding, terahertz time-domain spectroscopy (THz-TDS) is used to study oil–water two-phase flows with the input water fraction ranging from 0.5 to 5.0%. The flow rate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The signals transmitting through the chip show the presence of peak trough intensity features at different Re . As expected, the signal loss increases with the increase of Re , but it seems to occur in two-phases which is consistent with the results in our previous research [ 14 ]: a first fast phase until Re reaches about 250, and next a second phase showing a slower signal loss. Then the question arises why, although the flow seems to be in the laminar range, there is such an inversion point in the E P changing along with Re .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The signals transmitting through the chip show the presence of peak trough intensity features at different Re . As expected, the signal loss increases with the increase of Re , but it seems to occur in two-phases which is consistent with the results in our previous research [ 14 ]: a first fast phase until Re reaches about 250, and next a second phase showing a slower signal loss. Then the question arises why, although the flow seems to be in the laminar range, there is such an inversion point in the E P changing along with Re .…”
Section: Resultssupporting
confidence: 92%
“…However, there is still little research on understanding the characteristics and affecting factors of the flow in microchannels by terahertz time-domain spectroscopy (THz-TDS). Preliminary studies on the flow pattern and the slip phenomenon for oil-water two phase flow in macroscale pipes based on THz-TDS have been made previously [ 13 , 14 ]. Owing to the sensitivity of THz waves to the fluctuations of water dipole moments occurring on the picosecond (ps) timescale, THz technology can detect the subtle changes of water [ 15 , 16 ], so attempts have been made to predict the flow pattern transition of single phase flow in a rectangular microchannel using a method based on THz-TDS in this work.…”
Section: Introductionmentioning
confidence: 99%
“…As a practical method exploited in petroleum geology and biology to characterize the structural and compositional properties, THz-TDS has a high signal-to-noise ratio and great sensitivity to polar molecules. A THz wave segment corresponds to molecular rotation, molecular low-frequency vibration, crystal lattice motion, and hydrogen-bond extension . The results of previous studies revealed that THz-TDS technology has become a widely used OM detection method .…”
Section: Introductionmentioning
confidence: 99%
“…Optical technology plays an important role in probing crude oils. Laser-induced ultrasonic technique is here proposed to characterize the process of pyrolysis in the oil shale, and it is also used to measure the full-range water content up to 100%. , In addition, terahertz technology was used to characterize the water content and distribution in high-water-cut crude oil, , probe disaggregation of crude oil in a magnetic field, and evaluate pattern transitions of oil-water two-phase flow. , …”
Section: Introductionmentioning
confidence: 99%